Evaluation of Electromagnetic Near-Field Measurement Technique as Non-Destructive Testing for Composite Structures - Hussein, A.R. (Institute of Physics Publishing, 2018)
Nowadays there is no viable non-destructive method that could detect flaws in complex composite products. Such a method could provide unique tools to allow engineers to minimize time consumption and cost during the evaluation of various product parameters without disturbing production. The latest research and development on propagation waves introduce micro, radio and millimetre waves as new potential non-destructive test methods for evaluation of mechanical flaws and prediction of failure in a product during production. This paper focuses on recent developments, usage, classification of electromagnetic waves under the range of radio frequency, millimetre and micro-waves. In addition, this paper reviews the application of propagation wave and proposed a new health monitoring technique based on Doppler Effect for vibration measurement in complex composite structures. Doppler Effect is influenced by dynamic behaviour of the composite structures and both are effect by flaws occurred inside the structure. Composite manufacturers, especially Aerospace industry are demanding these methods comprehensively inspect and evaluate the damages and defects in their products. Â© Published under licence by IOP Publishing Ltd.